The Significance of Ushul al-Fiqh and Maqashid Syari'ah Approaches in Reforming Islamic Law in Indonesia: A Critical Study of the Penal Code or Another Topic - Yusuf, Nasruddin; Jamal, Ridwan; Makka, Misbahul Munir (UIN Sunan Kalijaga, 2024)
The integration between Tasyri's Philosophy and Sharia Philosophy in the context of Islamic law reform in Indonesia is the main focus of this study, especially in understanding how Islamic legal values can be applied effectively in the modern legislation system. The urgency of reforming Islamic law to answer the challenges of the times and the importance of understanding the relationship between the principles of tasyri' – as the basis for the formation of law – and sharia as the entire Islamic legal system that governs the lives of Muslims, are emphasized in the introduction. This research uses a qualitative approach with normative analysis, combining literature studies, the study of classical legal texts, and the interpretation of the views of contemporary scholars in Indonesia. The data obtained were critically analyzed to identify how Tasyri and Sharia Philosophy principles can be adapted into legislation responsive to social changes and the Indonesian context. The study results show that integrating Tasyri' and Sharia Philosophy in the reform of Islamic law in Indonesia allows the application of Islamic law that is more relevant to the needs of the times and enriches the legislation process with a strong ethical and moral basis. The main challenge in this integration is ensuring harmony between classical texts and modern social realities in Indonesia so that Islamic law continues to function as a dynamic and adaptive system, as a representation of religious law. Integrasi antara Filsafat Tasyri' dan Filsafat Syariah dalam konteks reformasi hukum Islam di Indonesia menjadi fokus utama penelitian ini, terutama dalam memahami bagaimana nilai-nilai hukum Islam dapat diterapkan secara efektif dalam sistem legislasi modern. Urgensi reformasi hukum Islam untuk menjawab tantangan zaman dan pentingnya memahami hubungan antara prinsip-prinsip tasyri' – sebagai dasar pembentukan hukum – dan syariah sebagai sistem hukum Islam secara keseluruhan yang mengatur kehidupan umat Muslim, ditekankan dalam pengantar. Penelitian ini menggunakan pendekatan kualitatif dengan analisis normatif, menggabungkan studi literatur, studi teks hukum klasik, dan interpretasi pandangan ulama kontemporer di Indonesia. Data yang diperoleh dianalisis secara kritis untuk mengidentifikasi bagaimana prinsip-prinsip Tasyri' dan Filsafat Syariah dapat diadaptasi ke dalam legislasi yang responsif terhadap perubahan sosial dan konteks Indonesia. Hasil studi menunjukkan bahwa integrasi Tasyri' dan Filsafat Syariah dalam reformasi hukum Islam di Indonesia memungkinkan penerapan hukum Islam yang lebih relevan dengan kebutuhan zaman dan memperkaya proses legislasi dengan dasar etika dan moral yang kuat. Tantangan utama dalam integrasi ini adalah memastikan keselarasan antara teks-teks klasik dan realitas sosial modern di Indonesia sehingga hukum Islam tetap berfungsi sebagai sistem yang dinamis dan adaptif, sebagai representasi dari hukum agama.